2014
DOI: 10.1089/end.2013.0344
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Impact of Three-Dimensional Vision on Laparoscopic Performance

Abstract: 3D laparoscopic camera equipment results in a significant improvement in depth perception, spatial location, and precision of surgical performance compared with the conventional 2D camera equipment. With this improved quality of vision, even expert laparoscopic surgeons may benefit from 3D imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 12 publications
3
41
2
1
Order By: Relevance
“…However, laparoscopic surgery is more difficult to learn and requires different psychomotor skills than open laparotomy. In fact, the surgeons have to work in a three-dimensional space, but are guided by twodimensional images [6]. The development of high definition cameras does not eliminate the major limitation of two-dimensional (2D) laparoscopy: lack of depth perception and lose of spatial orientation with potential increasing the strain for the surgeon, the risk of errors and the operative time.…”
Section: Introductionmentioning
confidence: 99%
“…However, laparoscopic surgery is more difficult to learn and requires different psychomotor skills than open laparotomy. In fact, the surgeons have to work in a three-dimensional space, but are guided by twodimensional images [6]. The development of high definition cameras does not eliminate the major limitation of two-dimensional (2D) laparoscopy: lack of depth perception and lose of spatial orientation with potential increasing the strain for the surgeon, the risk of errors and the operative time.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, few studies have been reported suggesting overall a better surgical performance when using 3D systems during laparoscopic (nonrobotic) tasks in a preclinical setting (Table 3). [5][6][7][10][11][12][13][14] Findings from our study suggest that the use of 3D technology facilitates laparoscopic surgical performance of naïve surgeons during kidney procedures in a porcine model. Notably, this is the first study reported in urology using this type of preclinical in vivo model.…”
Section: Commentmentioning
confidence: 73%
“…Thus, laparoscopic hysterectomy was less preferred over the years. Previous studies did not reveal any significant benefits of laparoscopic hysterectomy when compared with VH; [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] however, most of these studies are outdated and as the TLH experience increases among gynecologists, the superiority of VH when compared with laparoscopic hysterectomy is slowly changing over time. [26] In a small sample size study conducted in Germany in 2007, it was observed that TLH takes longer compared with VH; however, it reduces the postoperative hospitalization duration and analgesic usage.…”
Section: Discussionmentioning
confidence: 99%
“…[9,10] Therefore, surgeons lose perceptions of depth and spatial orientations and thus experience higher visual and cognitive loads. [11][12][13] To overcome few of the challenges associated with laparoscopy, 3D imaging was developed as an alternative to conventional 2D imaging. [13][14][15][16][17] Although 3D technology was introduced in the early 1990s, it is yet to be implemented as a standard procedure in hospitals.…”
mentioning
confidence: 99%
See 1 more Smart Citation